Master planning of 10 existing hospitals in Malaysia under the funding of the Asian Development Bank Loan 980 MAL : a retrospective study - Mohd Nawawi, Norwina (2000)
The paper provide a retrospective study on the 10 master planning hospital projects experience in Malaysia under the ADB 980 MAL loan. The paper describe the infrastructure the Malaysian government had put together in undertaking the massive task of master planning the 10 hospitals. The paper highlight the process of appointing various project teams from the client and from the industry; the channel of communication and decision making process to ascertain project are run on schedule. The master planing process itself and the consecutive output as the outcome were described through project examples. The lessons learnt and contentions are summarised